2002
DOI: 10.1021/np020308z
|View full text |Cite
|
Sign up to set email alerts
|

New Icetexane and 20-Norabietane Diterpenes with Trypanocidal Activity from Dracocephalum komarovi

Abstract: Two new icetexane diterpenes, cyclocoulterone (1) and komaroviquinone (2), and a novel 20-norabietane diterpene, dracocephalone A (3), were isolated from Dracocephalum komarovi. Their structures were elucidated by extensive analyses of spectral data. Komaroviquinone (2) showed strong trypanocidal activity against epmastigotes of Trypanosoma cruzi, the causative agent of American trypanosomiasis, with a minimum lethal concentration of 0.4 micro M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 5 publications
0
63
0
2
Order By: Relevance
“…4). 13,31,32) The trypanocidal activities of the isolated compounds are summarized in 33) In fact, we found that 54 was reduced by T. cruzi old yellow enzyme (TcOYE) to its semiquinone radical, which subsequently generates superoxide anion radicals (Fig. 5).…”
Section: Diterpenesmentioning
confidence: 99%
“…4). 13,31,32) The trypanocidal activities of the isolated compounds are summarized in 33) In fact, we found that 54 was reduced by T. cruzi old yellow enzyme (TcOYE) to its semiquinone radical, which subsequently generates superoxide anion radicals (Fig. 5).…”
Section: Diterpenesmentioning
confidence: 99%
“…This compound showed strong in vitro trypanocidal activity against epimastigotes of Trypanosoma cruzi, the causative agent of Chagas' disease in Central and South America. 3 In addition to compound 1, a minor diterpene 2 was also isolated from the same plant which possesses a novel spiro-octahydroindene skeleton and was named komarovispirone (2). 4 Biogenetically, komarovispirone (2) may be derived from komaroviquinone (1) through a novel ring-contraction sequence as outlined in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, cyclization of the olefinic intermediate 3 with Pd(OAc) 2 , K 2 CO 3 and PPh 3 in acetonitrile under reflux was followed by oxidation of the methylene group to produce ketone 5, which was found to be in equilibrium with the hemiketal form 6 in solution. Further oxidation of the equilibrating mixture with silver oxide in dilute HNO 3 afforded (±)-komaroviquinone (1) as the major product in 68% yield for this last step (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…2) while Chemical investigation on these species resulted in the isolation of flavanoids, 3,4) terpenoids, [5][6][7] cinnamic acid derivatives 8) and volatile oils. 9,10) In our further phytochemical investigation on Dracocephalum peregrinum, we isolated three new flavonoid glucosides, Peregrinumin A (1), Peregrinumin B (2) and Peregrinumin C (3), and a new cyanogenic glucoside, Peregrinumcin A (4).…”
mentioning
confidence: 99%